Association between living arrangement and quality of life for older adults in the community - Alisson Fernandes Bolina; Mayssa da Conceição Araújo; Vanderlei José Haas; Darlene Mara dos Santos Tavares (Universidade de São Paulo, 2021)
Objective: to compare the sociodemographic and economic characteristics of the older adults in the community according to the living arrangement and to verify the association between the type of living arrangement and the quality of life scores. Method: a cross-sectional epidemiological study conducted with 796 older adults in the community. To assess quality of life (dependent variable), network and social support (adjustment variable), validated and applied chi-square tests, descriptive statistical analysis, multiple comparison analysis (ANOVA) and multiple linear regression model (p<0.05) were used. Results: the older adults who lived only with their spouses had better quality of life scores in all domains and facets, except in the death and dying domain, which did not show any significant difference. The lowest scores for quality of life were identified in the groups with the presence of children and, exceptionally, in the domain of social relationships and, in the facets death and dying and intimacy, those who lived alone had worse assessments. In the adjusted model, there was an association between the type of living arrangement and the different domains and facets of quality of life. Conclusion: living arrangement was associated with quality of life scores for older adults in the community, even after adjusting for the gender, age, number of morbidities, and social support variables.